A 7-methoxytacrine–4-pyridinealdoxime hybrid as a novel prophylactic agent with reactivation properties in organophosphate intoxication. Issue 4 (7th June 2016) - Nepovimova, E.; Korabecny, J.; Dolezal, R.; Nguyen, T. D.; Jun, D.; Soukup, O.; Pasdiorova, M.; Jost, P.; Muckova, L.; Malinak, D.; Gorecki, L.; Musilek, K.; et al.
Graphical Abstract: Abstract: Chemical warfare agents constitute an increasing threat to both military and civilian populations. Therefore, effective prophylactic approaches are urgently needed. Herein, we present a novel hybrid compound which is able not only to keep acetylcholinesterase resistant to organophosphate (OP) inhibitors, but also to serve as an enzyme reactivator in the case of OP intoxication.